Assessment of Noise Pollution in Different Hatbazars of Butwal City, Rupandehi, Nepal - Rayamajhi, Kamal Bahadur (Himalayan Physics, 2017)
The study was carried out to ascertain the level of noise pollution at five different hatbazars (periodic markets) of Butwal Sub-Metropolitan city by using Dick Smith Digital Sound Level Meter Q 1362 in the specific time from 4:00 PM to 5:00PM in the month of June 2016 on a hatbazar day and a usual day. The result shows that the heighest Leq of 79.8 dB(A) was observed on hatbazar day at Butwal hatbazar. However, on non hatbazar day the highest Leq of 71.9 dB(A) was observed at Purano bus park hatbazar. The lowest Leq of 64.9 dB(A) and 54.6 dB(A) were respectively observed on hatbazar day and non hatbazar day at Majhagaun hatbazar. The study shows that the noise level was found to be higher on hatbazar day as compared to non hatbazar day in all sampling sites. The commercial activities, crowd of people, unnecessary advertisement of goods, blasting of horns increase noise levels in hatbazars. The Himalayan Physics Vol. 6 & 7, April 2017 (61-64)